Presentation skills for students / Joan Van Emden & Lucinda Becker. - Van Emden, Joan.; Becker, Lucinda M. (Houndmills, Basinstoke, Hampshire ; New York, NY : Palgrave Macmillan, 2010)
"Presentation Skills for Students is a practical, accessible guide for all students in further or higher education. It discusses speaking effectively in seminars, tutorials and formal presentations and helps with career research including a practical step-by-step guide to a successful job interview. Regular checklists and the friendly down-to-earth style make this an ideal reference tool. The second edition: reflects the changes in technology; includes new material in the job search and job interviews chapter; highlights the hazards of using social networking sites; includes illustrations, which add both clarity and humor"--
Keywords: Public speaking; Interpersonal communication